Efficacy of Apatinib plus S-1 Therapy in the Treatment of Advanced Gastric Cancer Patients and the Effect on the Levels of Tumor Markers and Th1 and Th2-Like Cytokines. (27th April 2022) - Gu, Jishu; Ni, Xuejiao; Ji, Jinfeng; Wei, Guohua; Shi, Lei; Xu, Chunming
Abstract : Objective . To assess the efficacy of apatinib plus S-1 therapy in the treatment of advanced gastric cancer patients and the effect on the levels of tumor markers and Th1 and Th2-like cytokines. Methods . From October 2019 to December 2020, 100 patients with advanced gastric cancer assessed for eligibility were recruited and assigned at a ratio of 1 : 1 to receive either S-1 regimen (tegafur, gimeracil, and oteracil potassium capsules) (observation group) or apatinib plus S-1 therapy (experimental group). Outcome measures included clinical efficacy serum tumor marker levels, Th1 and Th2-like cytokine levels, time to progression (TTP), overall survival (OS), and adverse events. Results . The S-1 therapy plus apatinib was associated with a significantly higher efficacy versus S-1 therapy alone (P  < 0.05). The eligible patients given S-1 therapy plus apatinib showed significantly lower levels of serum carcinoembryonic antigen (CEA), glycoantigen 199 (CA199), and glycoantigen 125 (CA125) versus those receiving S-1 therapy (P  < 0.05). S-1 therapy plus apatinib outperformed the single therapy of S-1 therapy in mitigating the levels of interferon- γ (IFN- γ ), tumor necrosis factor- α (TNF- α ), interleukin-4 (IL-4), and interleukin-10 (IL-10) (P  < 0.05). There was no statistically significant difference in the incidence of adverse reactions between the two groups (P  > 0.05). S-1 therapy plus apatinib was associated with a significantly shorter TTP (5.2 ± 0.7 months) and a longer OS (9.3 ± 2.5 months) versus S-1 therapy alone (7.1 ± 1.3, 5.1 ± 1.3 months) (P  < 0.05). Conclusion . The efficacy of apatinib plus S-1 therapy showed better improvement in lowering the serum tumor marker levels and ameliorating the Th1 and Th2-like cytokine levels versus S-1 therapy alone, so it is worthy of clinical application.